Pendidikan Tasawuf Solusi Pembentukan Kecerdasan Spiritual dan Karakter - Mustofa, Ali (INOVATIF: Jurnal Penelitian Pendidikan, Agama dan Kebudayaan, 2018)
Education has role to provide human resources to have high intelctual, spiritual, and having good morals. However, the education has not succeeded as general. There many youths and tenagers misbehave such as interfere general tranquility such as: drunkenness, irregular racing, and adultery. This shows how weak their spiritual and morals. In othersides, non formal education, such as tasawuf is able to create human to be faith and have good morals. The kinds of tasawuf education are Syari’ah, Thariqah, Haqiqah and Ma’rifat.meanwhile tasawuf material is practicing wirid, praying and fasting, which aims to integrate body and soul, feeling the meaning of cleanliness heart and the whole character and then achieving the ma'rifat. In tasawuf education, the murshid or teacher teaching, guiding, and training his disciples in order to achieve the intended purpose, namely purification of soul (tazkiyah al-nafs), cleansing of heart (tasfiyah al-qalb) and self-approach to Allah (taqarrub to Allah). The tasawuf education methods which are not found in general education are Muhasabah, Talqin, Mujahadah, and Khalwat. Therefore, tasawuf education causes human spiritual characteristic, such as the ability to transcend, sanctify daily experience, and use spiritual potentials to solve problems, ability to be seen in various virtues, and cultivate good morals towards Allah, himself, fellow, environment and nation.